THE OPENING OF CONSTITUTIONAL INTERPRETATION TO THE COMMUNITY OF INTERPRETERS. RETHINKING THE THEMATIC PERTINENCE IN ACTIVE LEGITIMACY IN CONCENTRATED CONTROL ACTIONS (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2024)
The general objective of this work is to address the historical, legislative, doctrinal and jurisprudential evolution regarding constitutionality control, the paradigm of modern constitutionalism itself and the opening of constitutional interpretation to the community of interpreters. The choice is justified because the issues of access to the Federal Supreme Court (STF) as a constitutional court, responsible for the interpretation and final decision on the application of Brazilian constitutional law, are pressing issues that interest the entire society, ultimately submitted to the understanding approved by the Supreme Court. It highlights its importance based on the new constitutional paradigm inaugurated in 1988, by covering in the Constitution principles and procedural guarantees that previously had protection in infra-constitutional legislation. The Constitution significantly expanded the scope of the so-called constitutional jurisdiction, especially regarding concentrated constitutionality control mechanisms that have collective features in procedural terms. This broad spectrum of guarantees, as well as the provision of more appropriate instruments for their implementation, allowed a redefinition of the concept of citizenship and the formulation of new bases for the development of multi-individual rights. In this sense, Peter Häberle's notion of constitutional jurisdiction is focused on, based on the understanding that individuals and different social groups are interpreters of the Constitution, forming the open society of interpreters of the Constitution. It is justified because the judicialization of politics and all issues of a constitutional nature increase the STF's performance in all social spheres, with openness to interpreters of the Constitution being a condition for the legitimacy of constitutional jurisdiction. Despite its great importance, this breadth of social participation in the Supreme Court's jurisprudence is often not seen in the most comprehensive way, causing a reductionism in understanding that makes broad participation of the entire society difficult. In this sense, it is concluded that the creation of the thematic relevance applied by the STF to some legitimized in the filing of concentrated control actions seems mistaken, since it creates a procedural obstacle without support in the Federal Constitution, given the understanding that the Constitution must be interpreted by the community of interpreters in a broad way. The methodology used was the analytical-deductive method, using bibliographical material, doctrine, legislation, jurisprudence and other resources such as the internet and newspapers. As for the approach, the study is based on qualitative research.